Resveratrol as an inhibitor of pregnane X receptor (PXR): another lesson in PXR antagonism - Smutny, Tomas; Pavek, Petr (Journal of pharmacological sciences, 2014)
The pregnane X receptor (PXR) plays a central role in the regulation of metabolism. Only few PXR antagonists have been described and the mechanism of PXR inhibition is mostly hypothetical or believed to be allosteric. Resveratrol is now being discussed as a novel agent that is capable of attenuating the PXR-inducible expression of the CYP3A4 gene, although the mechanistic explanation has not been determined. We discuss herein the effect of resveratrol on PXR in the context of our data from a ligand binding assay and with respect to the effect of resveratrol on various cellular signaling pathways that are known to affect PXR.
Keywords: signální transdukce; Signal Transduction; Pregnane X Receptor; Resveratrol; exprese genu; resveratrol; Humans; Gene Expression; stilbeny; Molecular Targeted Therapy; cytochrom P-450 CYP3A; Antineoplastic Agents; pregnanový X receptor; rifampin; lidé; induktory cytochromu P450 CYP3A; Cytochrome P-450 CYP3A Inducers; objevování léků; Receptors, Steroid; Stilbenes; steroidní receptory; cílená molekulární terapie; protinádorové látky; Rifampin; Cytochrome P-450 CYP3A; Drug Discovery